In Possession of a True Romance (The Hi/Story of Merlin and Vivien in Malory, - Jukić-Gregurić, Tatjana (2000)

(untitled) (Array)
n a collection of essays entitled Passions of the Mind A.S.Byatt offers her view of the relation between (historical) fact and fiction in the 19th century; in her (fictional) Possession: a Romance she attempts a possession of this same relation and its implications in various historicisms of our own time. My aim in this paper is a further exploration of various "histories" in A.S.Byatt's romance, especially as exemplified by her rendering of the Merlin/Vivien story. The Merlin/Vivien story is probably the most complex intertextual network in Byatt's text, because it embraces a whole history of signification - starting with medieval historias of the Arthurian cycle as opposed to (or complemented with) the romances of the same; via its Renaissance revision by Thomas Malory; via its Victorian reenactment by Tennyson, Burne-Jones and Beardsley; and finally as adopted/adapted by A.S.Byatt. All the more so (according to Byatt quoting Hawthorne) since it is a romance, not a novel, which attempts "to connect a bygone time with the very present that is flitting away from us".